PEMANTAUAN MENTOK RIMBA (ASARCORNIS SCUTULATA) BERBASIS SISTEM INFORMASI GEOGRAFIS DI TAMAN NASIONAL WAY KAMBAS - Didik Kurniawan; Elly Lestari Rustiati; Anie Rose Irawati; Zacky Zeinel Ibad Muchlas (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
Forests play a major role in supporting the survival of all living things in the world. A sustainable forest area certainly makes the wildlife live, e.g mentok rimba. A Geographic Information System for Monitoring mentok rimba (Asarcornis scutulata) applying the V-model approach. This research was conducted under programme of Way Kambas National Park and ALeRT (Aliansi Lestari Rimba Terpadu). The purpose of this research is to assist the monitoring team in Way Kambas National Park for updating mentok rimba data. Black Box Testing and User Acceptance Testing were applied. A Geographic Information System (GIS) which contains the distribution of forest stagnation in Way Kambas National Park was built.